A TCP-based early regression index predicts the pathological response in neo-adjuvant radio-chemotherapy of rectal cancer. Issue 3 (September 2018) - Fiorino, Claudio; Gumina, Calogero; Passoni, Paolo; Palmisano, Anna; Broggi, Sara; Cattaneo, Giovanni M.; Di Chiara, Alessandra; Esposito, Antonio; Mori, Martina; Raso, Roberta; Ronzoni, Monica; Rosati, Riccardo; et al.
Abstract: Purpose: Introducing a radiobiological index based on early tumor regression during neo-adjuvant radio-chemotherapy (RCT, including oxaliplatin) of rectal adenocarcinoma and testing its discriminative power in predicting the tumor response. Methods: Seventy-four patients were treated with Helical Tomotherapy following an adaptive (ART) protocol (41.4 Gy/18 fr, 2.3 Gy/fr) delivering a simultaneous integrated boost on the residual tumor in the last 6 fractions up to 45.6 Gy. T2-weighted MRI were taken before (MRIpre ) and at mid (MRImid ) therapy and the corresponding tumor volumes were considered ( V pre, V mid ). The "Early Regression Index" ( ER I TCP = - ln [ ( 1 - ( V mid / V pre ) ) V pre ] ) was introduced and its discriminative power was assessed in terms of AUC, sensitivity/specificity, positive/negative predictive value (PPV/NPV). Two end-points were considered: (a) pathological complete response (pCR) or clinical complete response followed by watch-and-wait, (cCR); (b) limited response (residual vital cells (RVC) in the surgical specimen >10%). Results: Complete data were available for 65 patients: pCR, cCR and RVC >10% were 20, 2 and 19 respectively. The discriminative power of ERITCP was moderately high (AUC = 0.81/0.75 for /pCRorcCR/RVC >10% respectively, p < 0.0005). ERITCP was highly sensitive (86–89%) with very high NPV (90–94%). The discriminative power of ERITCP was confirmed on a subgroup of 44/65 patients when considering tumor volumes delineated by a skilled radiologist. Conclusion: A radiobiologically consistent index based on early regression showed high performances in predicting the pathological response after neo-adjuvant RCT for rectal cancer with relevant potentialities for ART/treatment customization.